Basal cell adenoma in upper lip: case report - Graziele Beanes; Liliane Lins; Antônio Fernando Pereira Falcão
Basal cell adenoma is a rare benign salivary gland neoplasm that accounts for 1 to 3 % of all salivary gland tumors. Most cases occur in major salivary glands and are rare in minor salivary glands. Describe a clinical case of basal cell adenoma. A 76-year-old Caucasian Brazilian woman presents with a slow-growing asymptomatic lesion of the upper lip. Physical examination revealed a nodular lesion 1.1 cm in size. The lesion was firm to palpation and the surrounding mucosa had normal color and appearance, without any ulceration. The tumor was surgically removed by excisional biopsy. Biopsy confirmed basal cell adenoma. A systematic literature review was carried out in PubMed, Lilacs and SciELO databases. The review included all articles published before 1992. Until 1991 no differentiation was made between basal cell adenoma and canalicular adenoma. Both pathologies were classified as monomorphic adenoma. This is the seventh case of upper lip basal cell adenoma reported in the literature between 1992 and 2014. Three of the seven cases reported were from Brazil.